2007
DOI: 10.1103/physrevb.76.214421
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of epitaxialFe3SiMgO(001)thin films

Abstract: The composition dependence of the magnetic as well as structural properties of epitaxial 4 -40 nm Fe 3 Si thin films on MgO͑001͒ have been investigated using ferromagnetic resonance, superconducting quantum interference device magnetometry, and magneto-optical Kerr effect. Magnetic anisotropy energy, g factor, and magnetization were determined for different samples with Si concentrations of 20%, 25%, or 30% at room temperature. Additionally, different annealing procedures were applied. The magnetization was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 43 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…And the uniaxial anisotropy contributed more than cubic anisotropy to the total energy in Fe 3 Si films. The anisotropy constants are smaller than the values of bulk Fe 3 Si, which is probably due to the Si excess in the Fe 3 Si films .…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…And the uniaxial anisotropy contributed more than cubic anisotropy to the total energy in Fe 3 Si films. The anisotropy constants are smaller than the values of bulk Fe 3 Si, which is probably due to the Si excess in the Fe 3 Si films .…”
Section: Resultsmentioning
confidence: 67%
“…However, the ϕ scan of Fe 3 Si(001) show peaks at ϕ = −180, 90, 0, 90, 180°. Thus, the Fe 3 Si(001) film was proved to be fabricated on MgO(001) with 45° in‐plane rotation . Hence the epitaxial relationship is confirmed to be Fe 3 Si(001)〈110〉||MgO(001)〈100〉, as shown in the inset of Fig.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Our results show that the FeCNT is indeed not homogeneous but is built from 300 to 400 nm long single‐crystalline segments. Based on the experimental results together with micromagnetic simulations, it can be concluded that each of these segments is a magnetically high quality Fe nanowire with almost the bulk properties of Fe . The single‐crystal aspect together with the very small linewidth obtained from measurements promotes the FeCNTs as appealing candidates for spin‐wave transport in magnonic applications.…”
Section: Introductionmentioning
confidence: 94%
“…6 Epitaxial Fe 3 Si growth on MgO(001) and on GaAs(001) was reported in previous works. 7,8 For a detailed analysis of the Fe 3 Si/GaAs(001) interface by means of CEMS, we have applied the 57 Fe 3 Si tracer layer technique. The position of 57 Fe-enriched probe layers (95% enriched in 57 Fe) with a nominal thickness of 7 atomic monolayers (ML) (4 ML correspond to the lattice constant of bulk Fe 3 Si, a Fe 3 Si ¼ 5:66Å) is shown in the insets of Fig.…”
mentioning
confidence: 99%